Penerapan Pasal 81 Poin 20 Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja Dalam Kontrak Antara Perusahaan Dengan Buruh/Pekerja Alih Daya Di Kota Mataram - Wahyu Putra Romadhon; H. Zaeni Asyhadie; M. Yazid Fathoni (Private Law, 2023)
The purpose of this research is to determine how the contract is implemented between companies and outsourced workers/laborers in the city of Mataram. This research is based on Article 81 Point 20 of Law Number 11 of 2020 concerning Job Creation which amends Article 66 of Law Number 13 of 2003 concerning Employment. This research method is a normative legal research method. In implementing the work agreement made by PT.251 CSS (Cakra Samawa Sakti) with outsourced workers/laborers, they still need implement paragraph 3 of Law Number 11 of 2020, which amends Article 66 of Law Number 13 of 2003.